Los tabarquinos - Fernández Álvarez, Óscar (Estudios Humanísticos. Historia, 2003)
Este trabajo presenta tres partes: la geografía, la historia del pueblo tabarquino, desde los orígenes hasta el siglo XX, y después se estudia el universo de la cultura tradicional de esta comunidad isleña. Abstract: This paper shows three related parts: the Tabarca village, Geography, origins and History towards the twentieth Century, and then, an analyse of the traditional culture of this islander community.